Apt pupil [compact disc, unabridged] - King, Stephen, 1947- (Penguin Audio, 2009)
In order to keep his identity as a Nazi war criminal a secret, Arthur Denker must tell stories of the holocaust to his neighborhood paperboy, Todd Bowden.